2014
DOI: 10.1089/neu.2013.3169
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NF-κB Mediates Astrocyte Swelling and Brain Edema in Traumatic Brain Injury

Abstract: Brain edema and associated increased intracranial pressure are major consequences of traumatic brain injury (TBI). While astrocyte swelling (cytotoxic edema) represents a major component of the brain edema in the early phase of TBI, its mechanisms are unclear. One factor known to be activated by trauma is nuclear factor-jB (NF-jB). Because this factor has been implicated in the mechanism of cell swelling/brain edema in other neurological conditions, we examined whether NF-jB might also be involved in the media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 43 publications
3
67
0
Order By: Relevance
“…Additionally, we previously documented that following in vitro mechanical trauma to cultured astrocytes, changes in various intracellular signaling systems, as well as in cell swelling occurred [2730], and that such changes correlated well with in vivo findings [41, 32]. Altogether, these findings strongly suggest that our in vitro cell injury system is indeed a highly suitable system for investigating mechanisms of trauma-induced injury to neural cells.…”
Section: Methodssupporting
confidence: 76%
See 3 more Smart Citations
“…Additionally, we previously documented that following in vitro mechanical trauma to cultured astrocytes, changes in various intracellular signaling systems, as well as in cell swelling occurred [2730], and that such changes correlated well with in vivo findings [41, 32]. Altogether, these findings strongly suggest that our in vitro cell injury system is indeed a highly suitable system for investigating mechanisms of trauma-induced injury to neural cells.…”
Section: Methodssupporting
confidence: 76%
“…The in vitro system has the unique advantage of clearly delineating mechanisms and analyzing the responses to trauma in different cell types (neurons and astrocytes). We have found that this system reliably produces consistent degrees of traumatic injury [2830]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pattern recognition receptor-mediated NFκB signaling in astrocytes also results in cell swelling implicated in cytotoxic edema, a major pathophysiologic mechanism underlying the harmful increase in intracranial pressure following TBI (Jayakumar et al, 2014). Correspondingly, HMGB1 release following TBI-induced tissue damage can signal to microglia, inducing secretion of IL-6 that signals reactive astrocytes to upregulate the AQP4 water channel involved in astroglial water uptake (Laird et al, 2014).…”
Section: Reactive Astrocytes Regulate Tbi-associated Inflammationmentioning
confidence: 99%